Language Teacher Identity Tensions Nexus of Agency, Emotion, and Investment - Tajeddin, Zia; Yazan, Bedrettin (Routledge Research in Language Education, 2024)
Addressing the critical issue of teacher identity tensions, this edited volume looks at the tensions between teachers' instructional beliefs, values, and priorities, and the contextual constraints and requirements. It examines how teachers deal with these tensions to avoid demotivation and burnout, which play a significant role in identity construction. Tensions are inseparable from growth and transformation but have the potential to disrupt teacher identity construction. Therefore, continual efforts to resolve tensions in teaching are inevitable. The process of resolution or reconciliation might be extended, and teachers could need support in that process to minimize the possible negative impacts on their identities. This process can simultaneously generate positive outcomes for teachers' growth and learning. Therefore, how teachers perceive, respond to, and grapple with tensions are critical experiences that offer windows into the complexities of teacher identity negotiation. The volume paints a picture of the personal, professional, and political dimensions of teacher identity tensions in various international contexts. The chapters draw on empirical studies with clear pedagogical implications to illustrate what identity tensions language teachers face in and outside the classroom during their career trajectory, how language teachers cope with identity tensions in their professional life, and how teacher educators can integrate identity tensions into teacher learning activities. This book is beneficial for students and lecturers in applied linguistics, educational linguistics, and educational psychology. It will also be helpful of interest to teacher educators, teacher education researchers, teacher supervisors, and MA and doctoral students interested in research on language teacher identity.